The Unit : my life fighting terrorists as one of America's most secret military operatives - Gamal, Adam; Kennedy, Kelly, 1970- (St. Martin's Press, 2024)
"The first and only book to ever be written by a member of America's most secret military unit--an explosive and unlikely story of immigration, service, and sacrifice. Inside our military is a team of operators whose work is so secretive that the name of the unit itself is classified. Highly-trained in warfare, self-defense, infiltration, and deep surveillance, "the Unit," as the Department of Defense has asked us to refer to it, has been responsible for preventing dozens of terrorist attacks in the Western world. Never before has a member of this unit shared their story - until now. From Adam Gamal, one of the only Muslim Arab Americans to serve inside "the Unit," comes a gripping firsthand account of our nation's most secretive military group. When Adam arrived in the United States at the age of nineteen, he spoke no English, and at 5'1" and 112 pounds, he was far from what you might expect of a soldier. But compelled into service by a debt he felt he owed to his new country, he rose through the ranks of the military to become one of its most elite and skilled operators. With humor and humility, Adam shares stories of life-threatening injuries, of the camaraderie and capabilities of his team, of the incredible missions--but also of the growth he experienced as he learned to adhere to more moderate Islamic beliefs. Enthralling and eye-opening, The Unit is at once a gripping account of the fight against terror and an urgent examination of the need for diversity"--